Toward an environmental friendly operation of the CBM-TOF system - Deppner, Ingo Martin; Bogdan, Claudia; Brad, Sebastian; Brill, Cătălin; Dorobanţu, Daniel; Grafov, Aleksandr; Han, Dong; Herrmann, Norbert; Hu, Dongdong; Lazar, Alin; Li, Wen; Petriş, Mariana; et al. (The European physical journal. Plus, 2023)
The future fixed target high-rate compressed baryonic matter (CBM) experiment is one of the experimental pillars of the Facility for Antiproton and Ion Research (FAIR) located in Darmstadt/Germany. In order to provide an excellent particle identification (PID) of charged hadrons, the CBM-time-of-flight (TOF) group has developed a concept of a 120 m$$^2$$large TOF wall with a system time resolution below 80 ps based on multi-gap resistive plate chambers (MRPC). Currently, timing MRPC systems are operated with a gas mixture based on tetrafluoroethane (R134a, C$$_2$$H$$_2$$F$$_4$$) with additions of few vol% quencher gases, e.g., sulfur hexafluoride (SF$$_6$$) or/and isobutane (i-C$$_4$$H$$_10$$). Unfortunately, these gas mixtures have a high global warming potential (GWP) in the order of 1500, and therefore, strategies to reduce the environmental impact have to be developed. The various possibilities, including studies on eco-friendly gases, and the considered strategy by the CBM-TOF group will be elaborated in this article.